Electrochemically induced chemically reversible proton-coupled electron transfer reactions of riboflavin (vitamin B2) - Tan, Serena L. J. (2013)
The electrochemical behavior of the naturally occurring vitamin B2, riboflavin (Flox), was examined in detail in dimethyl sulfoxide solutions using variable scan rate cyclic voltammetry (ν = 0.1 – 20 V s–1) and has been found to undergo a series of proton-coupled electron transfer reactions. At a scan rate of 0.1 V s–1, riboflavin is initially reduced by one electron to form the radical anion (Flrad•–) at E0f = −1.22 V versus Fc/Fc+ (E0f = formal reduction potential and Fc = ferrocene). Flrad•– undergoes a homogeneous proton transfer reaction with the starting material (Flox) to produce FlradH• and Flox–, which are both able to undergo further reduction at the electrode surface to form FlredH– (E0f = −1.05 V vs Fc/Fc+) and Flrad•2– (E0f = −1.62 V vs Fc/Fc+), respectively. At faster voltammetric scan rates, the homogeneous reaction between Flrad•– and Flox begins to be outrun, which leads to the detection of a voltammetric peak at more negative potentials associated with the one-electron reduction of Flrad•– to form Flred2– (E0f = −1.98 V vs Fc/Fc+). The variable scan rate voltammetric data were modeled quantitatively using digital simulation techniques based on an interconnecting “scheme of squares” mechanism, which enabled the four formal potentials as well as the equilibrium and rate constants associated with four homogeneous reactions to be determined. Extended time-scale controlled potential electrolysis (t > hours) and spectroscopic (EPR and in situ UV–vis) experiments confirmed that the chemical reactions were completely chemically reversible.